Two Methods of AuNPs Synthesis Induce Differential Vascular Effects. The Role of the Endothelial Glycocalyx - Maldonado-Ortega, Daniel Alberto; Martínez-Castañón, Gabriel; Palestino, Gabriela; Navarro-Tovar, Gabriela; Gonzalez, Carmen (Frontiers in Medicine, 2022)
AuNPs are synthesized through several methods to tune their physicochemical properties. Although AuNPs are considered biocompatible, a change in morphology or properties can modify their biological impact. In this work, AuNPs (~12 to 16 nm) capping with either sodium citrate (CA) or gallic acid (GA) were evaluated in a rat aorta ex vivo model, in which endothelial inner layer surface is formed by glycocalyx (hyaluronic acid, HA, as the main component), promoting vascular processes, most of them dependent on nitric oxide (NO) production. Results showed that contractile effects were more evident with AuNPsCA, while dilator effects predominated with AuNPsGA. Furthermore, treatments with AuNPsCA and AuNPsGA in the presence or absence of glycocalyx changed the NO levels, differently. This work contributes to understanding the biological effects of AuNPs with different capping agents, as well as the key role of HA in the vascular effects induced by AuNPs in potential biomedical applications.